Foreign Competition, Skill Premium, and Product Quality: Impact of Chinese Competition on Mexican Plants - Thi Hang Banh; Mauro Caselli (Global Labor Organization (GLO), 2022)
This paper analyses the effect of rising competition from Chinese exports on the skill premium of Mexican plants. Using detailed product-plant-level production data from Mexico and bilateral product-level trade data for 1994-2007, we provide evidence that Mexican plants reduce their skill premium in response to increasing competition from Chinese exports, and the effect is more pronounced among non-exporting plants. Thus, we develop a model linking competition and wage inequality between skilled and unskilled workers by introducing these two types of labour to a model with heterogeneous firms and quality differentiation. Our model predicts that tougher competition leads plants to downgrade quality, which induces a decline in the wage difference between skilled and unskilled workers. We investigate this hypothesis empirically by analysing the effect of Chinese competition on the product quality of Mexican plants. Consistent with the fall in the skill premium, we document a downgrading impact of China's rise on Mexican plants' product quality and this quality downgrading is less intense for products sold in the foreign market. These findings provide empirical support for the predictions of our model.
Keywords: D21; D22; F12; F14; 330; product quality; Chinese competition; skill premium; Mexico; heterogeneous firms